2004
DOI: 10.1080/07315724.2004.10719417
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cellular Magnesium Nano-Analysis in Treatment of Clinical Magnesium Deficiency

Abstract: A novel technique, using energy dispersive X-ray microanalysis (EXAtm), for noninvasive intracellular (i.c.) measurement of magnesium [Mg2+]i has now been accomplished and proven to be a valuable tool in multiple aspects of normal as well as pathological magnesium metabolism. Since only 1% of total body Mg2+ is found in the intravascular space, serum levels of Mg2+ give little information about a patient's overall Mg2+ status with respect to this essential mineral. Using the EXAtm analysis it has shown been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Of interest is a non-invasive method using energy dispersive X-ray microanalysis for cellular Mg analysis in sublingual epithelial cells [101]. Changes in intracellular Mg concentrations measured by this method strongly correlate with changes in intracellular Mg from the myocardium [101]. Furthermore, sublingual epithelial cell Mg content has been reported to correlate with effectiveness of Mg supplementation therapy [101].…”
Section: Relevance Of Mg Deficiency In the Clinical Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…Of interest is a non-invasive method using energy dispersive X-ray microanalysis for cellular Mg analysis in sublingual epithelial cells [101]. Changes in intracellular Mg concentrations measured by this method strongly correlate with changes in intracellular Mg from the myocardium [101]. Furthermore, sublingual epithelial cell Mg content has been reported to correlate with effectiveness of Mg supplementation therapy [101].…”
Section: Relevance Of Mg Deficiency In the Clinical Settingmentioning
confidence: 98%
“…To overcome this limitation, it has been suggested that hypomagnesemia exits when serum levels of Mg are less than 0.9 mmol/L if accompanied by relevant symptoms [100]. Of interest is a non-invasive method using energy dispersive X-ray microanalysis for cellular Mg analysis in sublingual epithelial cells [101]. Changes in intracellular Mg concentrations measured by this method strongly correlate with changes in intracellular Mg from the myocardium [101].…”
Section: Relevance Of Mg Deficiency In the Clinical Settingmentioning
confidence: 98%
“…Silver et al 18 showed a significant correlation between the magnesium values in heart muscle biopsies from bypass surgery, with the values measured in 12,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that intracellular levels of Mg are low, despite normal serum dosage, since serum dosage corresponds to only 0.3% of total magnesium. It would be interesting to find out minimally invasive, accurate methods to detect intracellular Mg levels 18 to better understand many diseases, including cardiac arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation